Effective ways of using Technology in Teaching - Mourya, Surinder Kumar; Singh, Tarandeep (Gyan Management Journal, 2022)
During last two decades, technology has evolved and is still evolv ing. Many people are becoming technologically adept and digital citizens. Technology is essential to the creation and exchange of knowledge in the teaching sector in the current digital era. When technology is used in the classroom, it may improve teacher knowledge and aid in the learning and motivation of the students. Social networking has been used to support teaching over the past ten years, including its integration with online games and educational content (Johnson & Germain-Froese, 2016). Technology has also demonstrated its efficacy in the classroom, serving as a source of inspiration and creating an environment conducive to real learning. But there are still drawbacks to using technology in the classroom. Students might misuse technology and easily become distracted. In addition, exces sive use of technology may impair students’ ability to think (Fetylyana Nor Pazilah, 2019). This study looked at the best practices for integrating technology into the classroom. It aims to identify the most efficient online platforms and technological resources that teachers can use in their line of work. For creating educational content, many of these tools are free and simple to use. The purpose of this study is to determine how much aware ness there is among teachers and students at various colleges regarding the use of technology in the classroom.